Perangkat Lunak Mata Pelajaran IPS Kelas XI Berbasis Mobile Di SMA LTI IGM Palembang Dengan Metode User centered design - Fakhri Lambardo; Sutra Romadon (LPPM STIKOM Tunas Bangsa, 2024)
Education, especially vocational, currently needs to make various changes in the learning process, one of which is by applying different learning concepts Where in this learning students become active and dynamic parties in finding and managing sources of information related to existing learning material, getting conclusions on the material learned, and being able to apply independently what has been learned. The development of sophisticated technology today many people who have mobile phones or smartphones that are used to communicate, even have more than one. This opportunity is what we can use to learn from building an application using mobile phone programming. There are so many mobile platforms that exist today, one of which is booming is Android mobile. Android is a Linux-based operating system whose application programming language we can create using Java.